Kajian Ketersediaan Air Permukaan pada Beberapa Daerah Aliran Sungai (Studi Kasus di Sub DAS Temon, Wuryantoro, Alang, dan Keduang) - Ugro Hari Murtiono (Universitas Muhammadiyah Surakarta, 2009)
The study was conducted at some watersheds (Temon, Wuryantoro, Alang, and Keduang sub Watersheds), in Wonogiri District. These four sub Watersheds are Main River whose outlets go into Wonogiri Dam. The study will calculate of water availability and the need of water for various uses at four sub Watersheds. The Thornwaite and Mather method was used to calculate the of water availability. The results indicate that : (1) The water availability at Temon Sub Watershed) 35.435.875 m³ and the need of water per year sebesar 51.053.247 m³, the water minus 30,59% per year; (2) The water availability per year Wuryantoro sub Watershed 17.788.417 m³ and the need of water per year 22.413.430 m³, the water minus 20,64% per year; (3) The water availability per year at Alang sub Watershed 31.372.317 m³ per year and the need of water per year 69.566.500 m³, the water minus 54,90% per year; (4) The water availability per year geological at Keduang sub Watershed 438.527.889 m³ and the need of water per year 452.611.219 m³, the water minus 3,11% per year; (5). Watershed having condition needs improvement especially an effective water resourcesplan, allocating, and distributing of water according to priority establishment, e.g., water pond, revegetation with low evapotranspiration potential, developing infiltration well, protecting water spring from disconcerting, and construction of water reservoir.